The development and deployment of a maintenance operations safety survey - Langer, Marie; Braithwaite, Graham (Sage, 2016)
Objective: Based on the line operations safety audit (LOSA), two studies were conducted to develop and deploy an equivalent tool for aircraft maintenance: the maintenance operations safety survey (MOSS). Background: Safety in aircraft maintenance is currently measured reactively, based on the number of audit findings, reportable events, incidents, or accidents. Proactive safety tools designed for monitoring routine operations, such as flight data monitoring and LOSA, have been developed predominantly for flight operations. Method: In Study 1, development of MOSS, 12 test peer-to-peer observations were collected to investigate the practicalities of this approach. In Study 2, deployment of MOSS, seven expert observers collected 56 peer-to-peer observations of line maintenance checks at four stations. Narrative data were coded and analyzed according to the threat and error management (TEM) framework. Results: In Study 1, a line check was identified as a suitable unit of observation. Communication and third-party data management were the key factors in gaining maintainer trust. Study 2 identified that on average, maintainers experienced 7.8 threats (operational complexities) and committed 2.5 errors per observation. The majority of threats and errors were inconsequential. Links between specific threats and errors leading to 36 undesired states were established. Conclusion: This research demonstrates that observations of routine maintenance operations are feasible. TEM-based results highlight successful management strategies that maintainers employ on a day-to-day basis. Application: MOSS is a novel approach for safety data collection and analysis. It helps practitioners understand the nature of maintenance errors, promote an informed culture, and support safety management systems in the maintenance domain.
Keywords: LOSA; MOSS; threat and error management; peer-to-peer observation; undesired state